The Effect of High-Intensity Functional Training (HIFT) to Improve the Shooting Accuracy of Students in Elementary School Futsal Extracurricular Activities - Faizal Syahrulah; Dinar Dinangsit; Aam Ali Rahman (Universitas Tadulako, 2026)
Research on improving shooting precision in elementary school futsal extracurricular activities is still dominated by technical training, while approaches that integrate biomotor capacity development and engineering skills through High-Intensity Functional Training (HIFT) are still limited. This study aims to analyze the influence of HIFT on the shooting accuracy of students who participate in elementary school futsal extracurricular activities. The study uses a quantitative approach with a pre-experimental method through a One-Group Pretest–Posttest design. Participants consisted of 22 male students who were selected using the total sampling technique. The HIFT program is carried out for eight weeks with a frequency of two exercises each week based on the principles of Frequency, Intensity, Time, and Type (FITT) and progressive loads. Data were collected using a futsal precision shooting test that had been adapted and analyzed using descriptive statistics, Shapiro–Wilk normality test, paired sample t-test, and effect size analysis. The results showed that the average score of shooting accuracy increased from 16.00 ± 4.65 to 21.82 ± 2.81, or an increase of 5.82 points (36.4%). The peer-samples t-test showed a significant increase (t(21) = 5.41; p < 0.001), while Cohen's value d = 1.15 showed a large effect. These findings show that HIFT is not only effective in improving statistically precise shooting accuracy, but also provides high practical benefits through the integrated development of various biomotor components. This study provides empirical evidence that HIFT can be effectively applied to elementary school students as a training model that integrates the development of physical abilities and technical skills, so that it can be an alternative for physical education teachers and futsal coaches in designing more effective and efficient extracurricular training programs.